Self-stopping polishing compositions and methods

The CMP composition with cubic ceria abrasive particles, autostop agents, and cationic polymers addresses the challenge of high removal rates and efficient planarization in silicon-containing substrates, enhancing throughput and reducing trench losses through auto-shutdown behavior.

JP7611246B2Active Publication Date: 2025-01-09CMC MATERIALS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022523604
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-22
Filing Date
2020-10-22
Publication Date
2025-01-09
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

Existing chemical mechanical polishing (CMP) compositions for silicon-containing substrates, particularly ceria abrasive-based ones, lack effective methods to achieve high removal rates of patterned dielectric materials while maintaining low trench losses and efficient planarization, leading to issues with overpolishing and reduced throughput.

Method used

A CMP composition comprising cubic ceria abrasive particles, an autostop agent, and a cationic polymer, which provides improved active oxide removal rates, enhances planarization efficiency, and exhibits self-shutdown behavior by adjusting the removal rate as the substrate becomes planar.

Benefits of technology

The composition achieves significant improvements in active oxide removal rates, reduces trench losses, and ensures precise planarization with auto-shutdown capabilities, thereby increasing throughput and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611246000011
    Figure 0007611246000011
  • Figure 0007611246000012
    Figure 0007611246000012
  • Figure 0007611246000013
    Figure 0007611246000013
Patent Text Reader

Abstract

A chemical-mechanical polishing composition for polishing a substrate having a silicon oxide material, comprising, consisting of, or consisting essentially of a liquid carrier, cubic abrasive particles dispersed in the liquid carrier, an autoclaving agent, and a cationic polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 62 / 924,342, filed October 22, 2019, entitled “Self-Stopping Polishing Composition and Method.” [Background technology]

[0002] Chemical mechanical polishing is an important enabling technology in the fabrication of integrated circuits (ICs) and microelectromechanical systems (MEMS). CMP compositions and methods for polishing (or planarizing) the surface of a substrate (e.g., a wafer) are well known to those skilled in the art. Polishing compositions (also known as polishing slurries, CMP slurries, and CMP compositions) generally contain abrasive particles suspended (dispersed) in an aqueous solution to increase the material removal rate, improve the planarization efficiency, and / or reduce the defectivity during the CMP operation.

[0003] In certain polishing applications, it is desirable for the CMP composition to exhibit "self-stopping" such that the removal rate slows down once a high percentage of the surface "high points" (i.e., elevated regions) have been removed. In self-stopping polishing applications, the removal rate is effectively high when a significant step height is present on the substrate surface, and then decreases as the surface becomes essentially planarized. In various dielectric polishing steps (e.g., in STI processes), the removal rate of the patterned dielectric material (e.g., dielectric layer) is typically the rate-limiting factor of the overall process. Thus, a high removal rate of the patterned dielectric material is desired to increase throughput. Good efficiency in the form of relatively low trench loss is also desirable. Furthermore, if the removal rate of the dielectric material remains high even after planarization is reached, overpolishing occurs, resulting in increased trench loss.

[0004] The benefits of auto-stop slurries come from a reduced blanket removal rate, which creates a wider endpoint window. For example, the auto-stop behavior allows for the polishing of substrates with reduced dielectric film thickness, allowing reduced amounts of material to be deposited on structured underlayers. Motor torque endpoint detection can also be used for more effective monitoring of the final topography. By avoiding overpolishing or unnecessary removal of dielectric after planarization, the substrate can be polished with lower trench loss.

[0005] Cerium oxide (ceria) abrasives are well known in the industry, particularly for polishing silicon-containing substrates, including silicon oxide materials, such as tetraethyl orthosilicate (TEOS), silicon nitride, and / or polysilicon. Ceria abrasive compositions are widely used for advanced dielectric applications, including shallow trench isolation applications. Although the use of ceria abrasives is known, there remains a need for improved ceria abrasive-based CMP compositions. In particular, there remains a need for compositions and methods for chemically mechanically polishing silicon oxide-containing substrates that provide useful removal rates while also improving planarization efficiency. Summary of the Invention [Means for solving the problem]

[0006] A chemical mechanical polishing composition for polishing a substrate having a silicon-oxygen material (e.g., silicon oxide) is disclosed. In one embodiment, the polishing composition comprises, consists of, or consists essentially of a liquid carrier, cubic abrasive particles dispersed in the liquid carrier, an autoclaving agent, and a cationic polymer. Effect of the Invention

[0007] For a more complete understanding of the disclosed subject matter and its advantages, reference is made to the following detailed description taken in conjunction with the accompanying drawings, in which: [Brief description of the drawings]

[0008] [Figure 1] 1 and 2 are transmission electron microscopy (TEM) micrographs of a cubic ceria abrasive sample showing ceria abrasive particles with square faces. [Diagram 2] 1 and 2 are transmission electron microscopy (TEM) micrographs of a cubic ceria abrasive sample showing ceria abrasive particles with square faces. [Diagram 3] FIG. 3 is a scanning electron microscopy (SEM) micrograph of a cubic ceria abrasive sample showing ceria abrasive particles with square faces. [Figure 4] FIG. 4 is a plot showing active loss in Å versus pattern type for the patterned wafers polished in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A chemical mechanical polishing composition for polishing a substrate having a silicon-oxygen material (e.g., silicon oxide) is disclosed. The polishing composition comprises, consists of, or consists essentially of a liquid carrier, cubic abrasive particles dispersed in the liquid carrier, an autostopper, and a cationic polymer. In one embodiment, the autostopper comprises benzhydroxamic acid, salicylhydroxamic acid, kojic acid, or potassium sorbate. In another embodiment, the cationic polymer comprises poly(vinyl imidazolium), poly(methacryloyloxyethyl trimethylammonium), polylysine, polyquaternium-7.

[0010] The disclosed polishing compositions and corresponding (CMP methods) can provide significant and unexpected advantages. For example, the disclosed compositions can significantly improve active oxide removal rates, which can improve throughput and save time and costs (i.e., via improved planarization times). The disclosed compositions can further improve planarization of a wide variety of patterned oxide structures. The disclosed compositions can further improve / reduce trench loss and improve auto-stop behavior (reduced blanket speed).

[0011] The polishing composition contains abrasive particles including cubic ceria abrasive particles suspended in a liquid carrier. By "cubic" it is meant that the ceria abrasive particles are in the form or shape of a cube, i.e., approximately cubic. In other words, the cubic ceria abrasive particles are cubic in shape and nature. However, it will be appreciated that the edge dimensions, corners, and corner angles do not have to be exactly or precisely perfect cubes. For example, the cubic abrasive particles may have slightly rounded or chipped corners, slightly rounded edges, edge dimensions that are not exactly equal to each other, corner angles that are not exactly 90 degrees, and / or minor irregularities, and still retain the basic shape of a cube. As can be readily seen by those skilled in the art (e.g., via scanning electron microscopy or transmission electron microscopy), the cubic ceria abrasive particles are generally cubic in shape with allowable tolerances for grain growth and deagglomeration.

[0012] 1, 2 and 3 show examples of cubic ceria abrasive particles. These transmission electron microscopy (TEM) and transmission electron microscopy (TEM) images show ceria abrasive particles having square faces. For example, in these images, the particle faces shown each include four edges having approximately the same length (e.g., within 20% of each other, or within 10 percent of each other, or less). Furthermore, the edges meet at the corners at approximately 90 degree angles (e.g., within about 80-100 degrees, or within about 85-95 degrees). As will be appreciated by those skilled in the art, in the TEM and SEM images, the majority of the abrasive particles shown are cubic in that they have square faces as defined above. Some of the particles may be observed to include defects, for example, on one or more corners. Again, the term cubic is not intended to represent ceria abrasive particles that are precisely cubic, but rather particles that are essentially generally cubic as defined above and shown in FIGS. 1, 2 and 3.

[0013] As used herein, a chemical mechanical polishing composition containing a cubic ceria abrasive is one in which at least 25 percent of the abrasive particles are essentially cubic (cubic in form or shape, as described above). In a preferred embodiment, at least 40 percent (e.g., at least 60 percent, or at least 80 percent) of the abrasive particles are essentially cubic. As described above, cubic ceria abrasive particles can be easily evaluated and counted using TEM or SEM images, for example, at magnifications of about 10,000 times to about 500,000 times. The abrasive particles shown in the SEM or TEM images have faces with four sides that are similar in length (e.g., within 20 percent of each other, as described above). The images also show that adjacent sides are approximately perpendicular, for example, forming an angle of about 90 degrees (e.g., also within the range of about 80 degrees to 100 degrees, as described above). To determine whether a ceria polishing composition contains cubic ceria abrasive particles, a large number of randomly selected particles (i.e., 200 or more) shall be observed by SEM or TEM to perform a statistical analysis to determine the percentage of particles having square faces. Retained particles should have images of them that are well visible on the micrograph. Some of the particles may exhibit some defects on the surface of the particle and / or on one or more of the corners of the particle, but still be counted as cubic.

[0014] The cubic ceria abrasive particles may be substantially pure ceria abrasive particles (within normal tolerances for impurities) or may be doped ceria abrasive particles. Doped ceria abrasive particles may contain interstitial dopants (dopants that occupy spaces in the lattice that are normally not occupied) or substitutional dopants (dopants that occupy spaces in the lattice that are normally occupied by cerium or oxygen atoms). Such dopants may include virtually any metal atom, including, for example, Ca, Mg, Zn, Zr, Sc, or Y.

[0015] In certain advantageous embodiments, the dopant may comprise one or more lanthanides, including, for example, lanthanum, praseodymium, neodymium, promethium, samarium, and the like. In a particularly preferred embodiment, the cubic ceria abrasive particles comprise a mixed oxide of cerium and lanthanum. The molar ratio of La to (La+Ce) in the mixed oxide abrasive particles may be from about 0.01 to about 0.15, for example from about 0.01 to about 0.12. Of course, such abrasive particles may additionally comprise other elements and / or oxides (e.g., as impurities). Such impurities may originate from raw materials or starting materials used during the preparation process of the abrasive particles. The total proportion of impurities is preferably less than 0.2% by weight of the particles. Residual nitrates are not considered as impurities.

[0016] In certain embodiments, the molar ratio of La to (La+Ce) may be from about 0.01 to about 0.04 (e.g., from about 0.02 to about 0.03). In one such embodiment, the cubic ceria abrasive particles contain about 2.5 mole % lanthanum oxide and about 97.5 mole % cerium oxide. In other embodiments, the molar ratio may be from about 0.08 to about 0.12 (e.g., from about 0.09 to about 0.11). In one such other embodiment, the cubic ceria abrasive particles contain about 10 mole % lanthanum oxide and about 90 mole % cerium oxide. The abrasive particles may be a single-phase solid solution in which lanthanum atoms substitute for cerium atoms in the cerium oxide crystal structure. In one embodiment, the solid solution exhibits a symmetrical X-ray diffraction pattern, with peaks located between about 27 degrees and about 29 degrees, shifted to a smaller angle than pure cerium oxide. A solid solution can be obtained when the temperature in the aging substep (described below) is above about 60° C. As used herein, the term "solid solution" means that X-ray diffraction shows only the pattern of the cerium oxide crystal structure, with or without shifts in the individual peaks, but without additional peaks that would indicate the presence of other phases.

[0017] The cubic ceria abrasive particles may optionally be characterized by their specific surface area, determined on the powder by nitrogen adsorption using the Brunauer-Emmett-Teller method (BET method), as disclosed in ASTM D3663-03 (reapproved in 2015). The specific surface area of ​​the abrasive particles is about 3 to about 14 m. 2 / g (for example, about 7 to about 13 m 2 / g, or about 8 to about 12 m 2 / g).

[0018] The cubic ceria abrasive particles can also be optionally characterized by their average particle size and / or particle size distribution. The average particle size of the abrasive particles can be about 50 nm to about 1000 nm (e.g., about 80 nm to about 500 nm, about 80 nm to about 250 nm, about 100 nm to about 250 nm, or about 150 nm to about 250 nm). In addition, the average particle size can be greater than about 50 nm (e.g., greater than about 80 nm or greater than about 100 nm). The average particle size can be determined via dynamic light scattering (DLS), which corresponds to the median particle size (D50). DLS measurements can be performed, for example, using a Zetasizer (available from Malvern Instruments). As will be appreciated by those skilled in the art, DLS measurements can significantly undercount small particles when measured in the presence of larger particles. For the cubic ceria abrasive particles disclosed herein, the DLS technique tends to undercount particles less than about 40 nm. Of course, the disclosed embodiments may contain many such small particles (<40 nm) that are not counted by DLS and therefore do not contribute to the average particle size.

[0019] Laser diffraction techniques can also be optionally used to characterize the particle size distribution. As will be appreciated by those skilled in the art, laser diffraction techniques also tend to undercount small particles (e.g., less than about 40 nm in the disclosed embodiments). Laser diffraction measurements can be performed, for example, using a Horiba LA-960 with a relative refractive index of 1.7. From the distribution obtained by laser diffraction measurements, various parameters can be obtained, including, for example, D10, D50, D90, D99, and the dispersion index (defined below). Based on laser diffraction measurements, the abrasive particles may include a median diameter (D50) of about 100 nm to about 700 nm (e.g., about 100 nm to about 200 nm). For example, the D50 may be about 100 nm to about 150 nm or about 150 nm to about 200 nm. D50 is the median diameter determined from the distribution obtained by laser diffraction.

[0020] The D10 of the cubic ceria abrasive particles can optionally be about 80 nm to about 400 nm (e.g., about 80 nm to about 250 nm, about 80 nm to about 150 nm, or about 100 nm to about 130 nm). Needless to say, D10 is the particle size obtained by laser diffraction, and is the particle size at which 10% of the particles have a diameter less than D10.

[0021] The D90 of the cubic ceria abrasive particles may optionally be about 150 nm to about 1200 nm (e.g., about 150 nm to about 1000 nm, about 150 to about 750 nm, about 150 to about 500 nm, about 150 to about 300 nm, or about 200 nm to about 300 nm). D90 is the particle size obtained by laser diffraction and represents the particle size at which 90% of the particles have a diameter less than D90. The D90 of mechanically deagglomerated abrasive particles may be less than about 300 nm.

[0022] The cubic ceria abrasive particles can optionally exhibit a low dispersion index. The "dispersion index" is defined by the following formula: Dispersion index=(D90-D10) / 2·D50 The dispersion index may be less than about 0.60, such as less than about 0.5, less than about 0.4, or less than about 0.30. The dispersion index of the mechanically deagglomerated abrasive particles may be less than about 0.30. Furthermore, D90 / D50 may be from about 1.3 to about 2 for the mechanically deagglomerated particles.

[0023] The D99 of the cubic ceria abrasive particles may optionally be about 150 nm to about 3000 nm (e.g., about 200 nm to about 2000 nm, about 200 nm to about 1800 nm, about 200 nm to about 1200 nm, about 200 nm to about 900 nm, about 200 nm to about 600 nm, about 200 to about 500 nm, or about 200 to about 400 nm). The D99 of the mechanically deagglomerated abrasive particles may be less than about 600 nm (e.g., less than about 500 or about 400). D99 is the particle size determined by laser diffraction and represents the particle size at which 99% of the particles have a diameter less than D99.

[0024] The abrasive particles can be prepared using virtually any suitable method suitable for producing cubic ceria abrasive particles. The disclosed embodiments relate to chemical mechanical polishing compositions containing such abrasive particles, and methods of polishing substrates using such abrasive particles, and are not limited to any particular particle production method. In a particular embodiment, cubic ceria abrasive particles can be prepared by precipitating cerium nitrate (and optionally other nitrates if a doped ceria abrasive is prepared). The precipitated material can then be grown under a particular temperature and pressure regime to promote the growth of cubic ceria abrasive particles. These particles can then be cleaned and deagglomerated. A dispersion of cubic ceria abrasive particles can then be prepared and used to formulate the chemical mechanical composition of the present invention.

[0025] In one advantageous embodiment, cubic cerium-lanthanum oxide abrasive particles can be prepared by precipitating nitrates of cerium and lanthanum. One such preparation method comprises the following steps: (i) mixing an aqueous solution of cerium nitrate with an aqueous base under an inert atmosphere; (ii) heating the mixture obtained in (i) under an inert atmosphere; (iii) optionally acidifying the heat treated mixture obtained in (ii); (iv) washing the solid material obtained in (ii) or (iii) with water; (v) mechanically treating the solid material obtained in (iv) to deagglomerate the ceria particles; Includes.

[0026] The cerium nitrate solution used in step (i) of the above process can be prepared by mixing aqueous solutions of cerium nitrate and lanthanum nitrate. III , Ce IV and La III and Ce relative to the total Ce IV The salt composition may be characterized by a molar ratio of about 1 / (500,000) to about 1 / (4,000). In one embodiment, the molar ratio may be about 1 / (100,000) to about 1 / (90,000). It is generally advantageous to use salts and components having a high purity, for example a purity of at least 99.5 or 99.9 percent by weight.

[0027] Step (i) comprises mixing / reacting an aqueous solution of cerium nitrate with an aqueous base. Hydroxide type bases may be advantageous, including, for example, hydroxides of alkali metals or alkaline earth metals and aqueous ammonia. Secondary, tertiary or quaternary amines may be used. The aqueous solution of the base may be previously degassed (deoxygenated) by bubbling with an inert gas. Mixing may be performed by introducing the aqueous solution of cerium nitrate into the aqueous base. Mixing is performed under an inert atmosphere, for example in a closed or semi-closed reactor with an inert gas (for example nitrogen or argon) purge. Mixing may be performed with stirring. The molar ratio of base to (Ce+La) may be from about 8.0 to about 30.0 (for example greater than about 9.0). Step (i) may further be performed at a temperature of 5° C. to about 50° C., for example at a temperature of about 20° C. to 25° C.

[0028] Step (ii) involves heating the mixture obtained at the end of the preceding step, and may include a heating substep and an ageing substep. The heating substep may involve heating the mixture to a temperature of from 75° C. to about 95° C., for example from about 85° C. to about 90° C. The ageing substep may involve maintaining (holding) the mixture at that temperature for about 2 hours to about 20 hours. Generally, the ageing time decreases with increasing temperature. Step (ii) may also be carried out under stirring under an inert atmosphere, as described above for step (i).

[0029] In step (iii), the mixture obtained at the end of step (ii) can be optionally acidified, for example using nitric acid. The heat-treated reaction mixture can be acidified, for example, to a pH of less than about 3.0 (e.g., from about 1.5 to about 2.5).

[0030] In step (iv), the solid material obtained in step (ii) or (iii) may be washed with water (e.g., deionized water). Washing can reduce residual nitrates in the final dispersion and achieve the target conductivity. Washing can include filtering the solids from the mixture and redispersing the solids in water. Filtration and redispersion can be performed several times if necessary.

[0031] In step (v), the washed solid material obtained in (iv) can be optionally mechanically treated to deagglomerate or partially deagglomerate the ceria abrasive particles, including, for example, double jet or ultrasonic deagglomeration, which typically results in a narrow particle size distribution and reduces the number of large agglomerated particles.

[0032] After step (iv) or (v), the solid material can be dried to obtain the cerium-based particles in powder form. The powder can be redispersed by adding water or a mixture of water and a miscible liquid organic compound, thereby obtaining a dispersion of the cerium-based particles in the liquid medium. The liquid medium can be water or a mixture of water and a water-miscible organic liquid. The water-miscible organic liquid can include, for example, alcohols such as isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol, ketones such as acetone, diacetone alcohol, methyl ethyl ketone, esters such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate. The ratio of water to organic liquid can be 80:20 to 99:1 parts by weight. Furthermore, the dispersion can include about 1 weight percent to about 40 weight percent, for example about 10 weight percent to about 35 weight percent, of the cerium-based particles. The dispersion may also have a conductivity of less than about 300 μS / cm, such as less than about 150 μS / cm, more specifically less than 150 μS / cm, or less than about 100 μS / cm.

[0033] The polishing composition may contain substantially any suitable amount of cubic ceria abrasive particles. For example, the polishing composition may contain about 0.001 weight percent (10 ppm) or more (e.g., about 0.002 weight percent or more, about 0.005 weight percent or more, about 0.01 weight percent or more, about 0.02 weight percent or more, about 0.05 weight percent or more, or about 0.1 weight percent or more) of cubic ceria abrasive particles at the point of use. The polishing composition may contain about 5 weight percent or less (e.g., about 2 weight percent or less, about 1.5 weight percent or less, about 1 weight percent or less, or about 0.5 weight percent or less) of cubic ceria abrasive particles at the point of use. Needless to say, the cubic ceria abrasive particles may be present in the polishing composition at a concentration that is bounded by any two of the aforementioned endpoints. For example, the concentration of cubic ceria abrasive particles in the polishing composition at the point of use can be about 0.001 weight percent to about 5 weight percent (e.g., about 0.005 weight percent to about 1 weight percent, about 0.01 weight percent to about 1 weight percent, or about 0.01 weight percent to about 0.5 weight percent).

[0034] An aqueous liquid carrier is used to facilitate application of the abrasive and any optional chemical additives to the surface of the substrate to be polished (e.g., planarized). By aqueous, it is meant that the liquid carrier consists of at least 50 wt% water (e.g., deionized water). The liquid carrier may include other suitable non-aqueous carriers, including lower alcohols (e.g., methanol, ethanol, etc.) and ethers (e.g., dioxane, tetrahydrofuran, etc.). Preferably, the liquid carrier consists essentially of or consists of water, more preferably deionized water.

[0035] The polishing composition is generally weakly acidic, neutral, or alkaline and has a pH of about 5 to about 10 (e.g., greater than about 5 and / or less than about 10). In certain embodiments, the polishing composition may be neutral or weakly alkaline and have a pH of about 6 to about 10 (e.g., about 6.5 to about 9.5, or about 7 to about 9). In such embodiments, the pH of the polishing composition may be about 8 (e.g., about 7.5 to about 8.5). In another embodiment, the polishing composition is weakly acidic or neutral and has a pH of about 5 to about 8 (e.g., about 5 to about 7, or about 5 to about 6.5). In one such embodiment, the pH of the polishing composition is about 5 (e.g., about 5.5 to about 6.5). In one embodiment, the disclosed embodiments enable excellent auto-shutoff performance at weakly acidic pH values.

[0036] The polishing composition includes an autostopper. Examples of autostoppers are disclosed in commonly assigned U.S. Patent Application Publication No. 2019 / 0185716. The autostopper facilitates a relatively high pattern removal rate and a relatively low blanket removal rate, and further facilitates the transition from a high pattern removal rate to a relatively low blanket removal rate during planarization of the substrate. For example, the autostopper may be a ligand bound to the cubic ceria abrasive particles. In some polishing applications, the concentration of the autostopper influences the observed results because at low concentrations, the autostopper can act as a rate enhancer (e.g., a "high" removal rate is observed), and at higher concentrations, autostop behavior is observed (e.g., a "stop" removal rate is observed). Thus, some autostoppers can have a dual effect. For example, when the polishing composition contains picolinic acid at a low concentration, the picolinic acid can function as a rate enhancer. However, when the polishing composition contains picolinic acid at a higher concentration, the picolinic acid can function as an autostopper. For example, picolinic acid can function as a rate enhancer at point-of-use concentrations of less than about 1000 ppm by weight.

[0037] In some embodiments of the invention, the autoterminating agent has the formula QB, where Q is a substituted or unsubstituted hydrophobic group or a sterically hindering group, and B is a linking group, such as -C(O)-C-OH, -C(O)-CC-OH, or -C(O)-OH. The linking group may be -C(O)-X-OH, where X is a C1-C2 alkyl group. When the autoterminating agent is a compound of formula QB described herein, Q may be any suitable hydrophobic group or any suitable sterically hindering group. Suitable hydrophobic groups include saturated and unsaturated hydrophobic groups. The hydrophobic groups may be linear or branched, and may include linear or branched alkyl groups, cycloalkyl groups, and ring structures including aromatic groups, heterocyclic groups, heteroaromatic groups, fused ring systems, and combinations thereof.

[0038] Q may be an alkyl group. Suitable alkyl groups are, for example, linear or branched, saturated or unsaturated, substituted or unsubstituted hydrocarbon groups having 1 to 30 carbon atoms (e.g., C1-C30 alkyl groups, C1-C24 alkyl groups, C1-C18 alkyl groups, C1-C12 alkyl groups, or C1-C6 alkyl groups), such as at least 1 carbon atom (i.e., methyl), at least 2 carbon atoms (i.e., ethyl, vinyl), at least 3 carbon atoms (i.e., propyl, isopropyl, propenyl, etc.), at least 4 carbon atoms (butyl, isobutyl, sec-butyl, butane, etc.), at least 5 carbon atoms (pentyl, isopentyl, and the like), hydrocarbon groups having at least 6 carbon atoms (e.g., hexyl), at least 7 carbon atoms, at least 8 carbon atoms, at least 9 carbon atoms, at least 10 carbon atoms, at least 11 carbon atoms, at least 12 carbon atoms, at least 13 carbon atoms, at least 14 carbon atoms, at least 15 carbon atoms, at least 16 carbon atoms, at least 17 carbon atoms, at least 18 carbon atoms, at least 19 carbon atoms, at least 20 carbon atoms, at least 25 carbon atoms, or at least 30 carbon atoms.

[0039] Substituent means a group in which one or more carbon-bonded hydrogen atoms are replaced by a non-hydrogen atom. Exemplary substituents include, for example, hydroxyl groups, keto groups, esters, amides, halogens (e.g., fluorine, chlorine, bromine, and iodine), amino groups (primary, secondary, tertiary, and / or quaternary), and combinations thereof.

[0040] Q may be a cycloalkyl group. Suitable cycloalkyl groups include, for example, saturated or unsaturated, substituted or unsubstituted cycloalkyl groups having 3 to 20 carbon atoms (e.g., C3-C20 cyclic groups). For example, suitable cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and combinations thereof. In addition, suitable unsaturated cycloalkyl groups include, for example, cyclobutene, cyclopentene, cyclohexene, and combinations thereof.

[0041] Q may be an aromatic group. Suitable aromatic groups include, for example, substituted or unsubstituted aromatic groups having 1 to 20 carbon atoms. For example, suitable aromatic groups include phenyl, benzyl, naphthyl, azulene, anthracene, pyrene, and combinations thereof.

[0042] Q may be a heteroaromatic group. A "heteroatom" is defined herein as any atom other than carbon and hydrogen atoms. Suitable heteroatom-containing functional groups include, for example, hydroxyl groups, carboxylic acid groups, ester groups, ketone groups, amino groups (e.g., primary, secondary, and tertiary amino groups), amide groups, imide groups, thiol ester groups, thioether groups, nitrile groups, nitros groups, halogen groups, and combinations thereof.

[0043] Suitable heterocyclic groups include, for example, cyclic hydrocarbon compounds having 1 to 20 carbon atoms containing nitrogen, oxygen, sulfur, phosphorus, boron, and combinations thereof. Heterocyclic compounds can be saturated and unsaturated, substituted or unsubstituted. Heterocyclic compounds refer to 5-, 6-, or 7-membered ring compounds that contain one or more heteroatoms (e.g., N, O, S, P, or B) as part of the ring system. Exemplary heterocyclic compounds include, for example, triazole, aminotriazole, 3-amino-1,2,4-triazole, 3-amino-1,2,4-triazole-5-carboxylic acid, 3-amino-5-mercapto-1,2,4-triazole, 4-amino-5-hydrazino-1,2,4-triazole-3-thiol, thiazole, 2-amino-5-methylthiazole, 2-amino-4-thiazoleacetic acid, heterocyclic N-oxides, 2-hydroxypyridine-N-oxide, 4-methylmorpholine-N-oxide, and picolinic acid N-oxide, and the like. Other exemplary heterocyclic compounds include, for example, pyrone compounds, pyridine compounds, pyrrolidine, delta-2-pyrroline, imidazolidine, delta-2-imidazoline, delta-3-pyrazoline, piperidine, piperazine, morpholine, quinuclidine, indoline, isoindoline, chroman, isochroman, and combinations thereof, including positional and stereoisomers.

[0044] Suitable heteroaromatic groups include, for example, pyridine, thiophene, furan, pyrrole, 2H-pyrrole, imidazole, pyrazole, isoxazole, furazan, isothiazole, pyran (2H), pyrazine, pyrimidine, pyridazine, isobenzofuran, indolizine, indole, 3H-indole, 1H-indazole, purine, isoindole, 4aH-carbazole, carbazole, beta-carboline, 2H-chromene, 4H-quinolizine, isoquinoline, quinoline, quinoxaline, 1,8-naphthyridine, phthalazine, quinazoline, cinnoline, pteridine, xanthene, phenoxathiin, phenothiazine, phenazine, perimidine, 1,7-phenanthroline, phenanthridine, acridine, and combinations thereof.

[0045] In some embodiments, Q is substituted with one or more substituents. Suitable substituents may include, for example, any suitable compound / group described herein. For example, suitable substituents may include alkyl groups, cycloalkyl groups, aryl groups, heterocyclic groups, heteroaromatic groups, and combinations thereof.

[0046] In some embodiments, Q is unsubstituted. In other embodiments, Q is a sterically hindering group. For example, Q may be a bulky moiety that is not particularly hydrophobic and prevents chemical reactions or interactions that would otherwise occur within related molecules with smaller Q groups. Examples of autoterminating agents with such Q groups include maltol, ethyl maltol, and kojic acid.

[0047] In some embodiments, the linking group B is selected from a carboxylic acid group, a hydroxamic acid group, a hydroxylamine group, a hydroxyl group, a keto group, a sulfate group, a phosphate group, and combinations thereof.

[0048] In some embodiments, the auto-stop agent QB is selected from kojic acid, maltol, ethyl maltol, propyl maltol, hydroxamic acid, benzhydroxamic acid (benzohydroxamic acid), tiglic acid, angelic acid, salicylhydroxamic acid, benzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, caffeic acid, sorbic acid, potassium sorbate, and combinations thereof. Of course, salts of the auto-stop agent of formula QB are also suitable for use in the polishing composition of the present invention.

[0049] The polishing composition may contain any suitable amount of an auto-stop agent (e.g., a compound of formula QB). If the composition contains too little auto-stop agent, the composition may not exhibit suitable auto-stop behavior. Conversely, if the composition contains too much auto-stop agent, the composition may exhibit undesirable performance (e.g., low removal rate), may not be cost-effective, and / or may lack stability. One advantageous feature of the present invention is that the use of a stop agent in combination with cubic ceria abrasive particles allows the use of higher concentrations of the auto-stop agent. Such compositions of the present invention are advantageous because they allow for excellent active removal rates, excellent auto-stop behavior, and excellent planarization.

[0050] For example, the polishing composition may contain about 10 ppm by mass (0.001 percent by mass) or more (e.g., about 20 ppm by mass or more, about 50 ppm by mass or more, about 100 ppm by mass or more, about 200 ppm by mass or more, about 250 ppm by mass or more, or about 500 ppm by mass or more) of the autoclaving agent at the point of use. Thus, the polishing composition may contain about 10 ppm by mass to about 2 percent by mass of the autoclaving agent at the point of use. For example, the polishing composition may contain about 20 ppm by mass to about 1 percent by mass (10,000 ppm) (e.g., about 50 ppm by mass to about 10,000 ppm by mass, about 100 ppm by mass to about 10,000 ppm by mass, about 200 ppm by mass to about 5000 ppm by mass, or about 250 ppm by mass to about 2500 ppm by mass) of the autoclaving agent at the point of use. In certain advantageous embodiments, the polishing composition comprises from about 500 ppm to about 2000 ppm by weight of an autostop agent at the point of use.

[0051] The polishing composition may further comprise a cationic polymer (e.g., also referred to as a planarizing agent or a topography control agent). The cationic polymer may comprise virtually any suitable cationic polymer and may be selected from cationic homopolymers and / or cationic copolymers comprising at least one cationic monomer and at least one nonionic monomer.

[0052] The cationic homopolymer may be any suitable cationic homopolymer comprising a cationic monomer repeat unit comprising a quaternary amine group as a repeat unit. The quaternized amine group may be acyclic or may be incorporated into a ring structure. The quaternized amine group comprises a tetrasubstituted nitrogen atom substituted with four groups independently selected from alkyl, alkenyl, aryl, or arylalkyl groups. When incorporated into a ring structure, the quaternized amine group comprises a heterocyclic saturated ring containing a nitrogen atom and further substituted with two groups as described above, or a heteroaryl group (e.g., imidazole or pyridine) having an additional group as described above bonded to the nitrogen atom. The quaternized amine group has a positive charge (i.e., a cation with an associated anion moiety). It is also suitable for further modification of the cationic polymer by alkylation, acylation, ethoxylation, or other chemical reactions, thereby changing the solubility, viscosity, or other physical parameters of the cationic polymer. Suitable quaternized amine monomers include, for example, quaternized vinylimidazole (vinylimidazolium), poly(vinylimidazole), methacryloyloxyethyltrimethylammonium (MADQUAT), diallyldimethylammonium (DADMA), methacrylamidopropylmethylammonium (MAPTA), quaternized dimethylaminoethylmethacrylate (DMAEMA), and combinations thereof. Of course, MADQUAT, DADMA, MAPTA, and DMAEMA commonly include a counter anion, such as a carboxylate (e.g., acetate) or a halide anion (e.g., chloride). The disclosed embodiments are not limited in this respect.

[0053] The cationic polymer may be a copolymer comprising at least one cationic monomer (e.g., as described in the previous paragraph) and at least one non-ionic monomer. Non-limiting examples of suitable non-ionic monomers include vinylpyrrolidone, vinylcaprolactam, vinylimidazole, acrylamide, vinyl alcohol, polyvinylformal, polyvinylbutyral, poly(vinyl phenyl ketone), vinylpyridine, polyacrolein, ethylene, propylene, styrene, epichlorohydrin, and combinations thereof.

[0054] Examples of cationic polymers include, for example, poly(vinylimidazole), poly(vinylimidazolium), poly(methacryloyloxyethyltrimethylammonium) (polyMADQUAT), poly(diallyldimethylammonium) (e.g., polyDADMAC), poly(diallyldimethylammonium-co-acrylamide), poly(dimethylamine-co-epichlorohydrin), poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] (i.e., polyquaternium-1,3-diamine ... Polyquaternium-2), copolymers of vinylpyrrolidone and quaternized dimethylaminoethyl methacrylate (i.e., Polyquaternium-11), copolymers of vinylpyrrolidone and quaternized vinylimidazole (i.e., Polyquaternium-16), terpolymers of vinylcaprolactam, vinylpyrrolidone and quaternized vinylimidazole (i.e., Polyquaternium-46), and 3-methyl-1-vinylimidazolium methylsulfate-N-vinylpyrrolidone copolymer (i.e., Polyquaternium-44). Additionally, suitable cationic polymers include personal care cationic polymers such as Luviquat® Supreme, Luviquat® Hold, Luviquat® UltraCare, Luviquat® FC 370, Luviquat® FC 550, Luviquat® FC 552, Luviquat® Excellence, and combinations thereof.

[0055] In certain advantageous embodiments, the cationic polymer may include poly(methacryloyloxyethyltrimethylammonium), such as polyMADQUAT (e.g., Alco 4773), poly(vinylimidazolium), such as poly(vinylimidazolium) methylsulfate, and imidazolium compounds, such as Luviquat® Ultracare.

[0056] In certain embodiments, the cationic polymer may additionally or alternatively comprise amino acid monomers (such compounds may also be referred to as polyamino acid compounds). Suitable polyamino acid compounds may comprise virtually any suitable amino acid monomer group, including, for example, polyarginine, polyhistidine, polyalanine, polyglycine, polytyrosine, polyproline, and polylysine. In certain embodiments, polylysine may be the preferred cationic polymer. It goes without saying that polylysine may comprise ε-polylysine and / or α-polylysine, which are composed of D-lysine and / or L-lysine. Polylysine may thus comprise α-poly-L-lysine, α-poly-D-lysine, ε-poly-L-lysine, ε-poly-D-lysine, and combinations thereof. In certain embodiments, polylysine may be ε-poly-L-lysine. It also goes without saying that the polyamino acid compounds may be used in any available form. For example, conjugate acid or base and salt forms may be used instead of (or in addition to) polyamino acids.

[0057] The cationic polymer may also (or instead) comprise a derivatized polyamino acid (i.e., a cationic polymer containing derivatized amino acid monomer units). For example, the derivatized polyamino acid may comprise a derivatized polyarginine, a derivatized polyornithine, a derivatized polyhistidine, and / or a derivatized polylysine. CMP compositions are disclosed in U.S. Provisional Patent Application No. 62 / 958,033, which is incorporated herein by reference in its entirety.

[0058] In such embodiments, the derivatized amino acid monomer comprises a derivative group attached to the alpha amino group of the derivatized amino acid monomer. The derivative group may comprise virtually any suitable group, including, for example, alkylcarbonyl groups, divalent carboacyl groups, alkylurea groups, alkylsulfonate groups, alkylsulfone groups, and alkyl ester groups.

[0059] Examples of alkylcarbonyl groups include acetyl, pivaloyl, ethylcarbonyl, and the like. Examples of divalent carboacyl groups include succinyl, octenylsuccinyl, glutaric, methylsuccinyl, and the like. Among the divalent carboacyl groups, succinyl and glutaric groups may be preferred due to solubility. Examples of acryloyl groups include ethylurea, butylurea, cyclohexylurea, and the like. Examples of alkylsulfonate groups include methylsulfonate, dimethylsulfonate, ethylsulfonate, propylsulfonate, butylsulfonate, pentasulfonate, and the like. Examples of alkylsulfone groups include methylsulfone, ethylsulfone, propylsulfone, butylsulfone, pentasulfone, and the like. Examples of alkylester groups include methylester, ethylester, propylester, butylester, pentaester, and the like.

[0060] If present, cationic polymer can be present in the polishing composition at any suitable concentration.One advantageous feature of the present invention is that when cationic polymer is used in combination with cubic ceria abrasive particles, it allows the use of higher cationic polymer concentrations.Such compositions of the present invention are advantageous because they allow excellent active removal rate, excellent self-stopping behavior, and excellent planarization.

[0061] It has been found that the cationic polymer concentration is highly dependent on the particular cationic polymer selected, and may also depend on the cubic ceria abrasive particle concentration and the autostop agent concentration. Roughly speaking, the concentration of the cationic polymer at the point of use is about 1 ppm to about 1000 ppm by weight (e.g., about 5 ppm to about 500 ppm by weight). For example, when the cationic polymer is a poly(vinyl imidazolium) compound, such as poly(vinyl imidazolium) methyl sulfate, the composition may contain about 1 ppm to about 75 ppm by weight at the point of use. For example, the concentration of the cationic polymer may be about 5 ppm to about 75 ppm by weight (e.g., about 5 ppm to about 50 ppm by weight, about 5 ppm to about 40 ppm by weight, or about 10 ppm to about 40 ppm by weight).

[0062] In another example, when the cationic polymer includes a poly(methacryloyloxyethyltrimethylammonium) halide, such as polyMADQUAT, or an imidazolium compound, such as Luviquat® Ultracare, the composition may include about 25 ppm by mass to about 1000 ppm by mass at the point of use. For example, the concentration of the cationic polymer may be about 75 ppm by mass to about 500 ppm by mass (e.g., about 100 ppm by mass to about 500 ppm by mass, about 150 ppm by mass to about 500 ppm by mass, or about 200 ppm by mass to about 400 ppm by mass).

[0063] In yet another example, when the cationic polymer comprises a polyamino acid compound, such as ε-poly-D-lysine, the composition may comprise about 5 ppm by mass to about 500 ppm by mass at the point of use. For example, the concentration of the cationic polymer may be about 5 ppm by mass to about 400 ppm by mass (e.g., about 10 ppm by mass to about 300 ppm by mass, about 15 ppm by mass to about 200 ppm by mass, or about 20 ppm by mass to about 200 ppm by mass).

[0064] The polishing composition may further comprise a non-polymeric cationic compound (in addition to the cationic polymer). Suitable cationic compounds include 2-(dimethylamino)ethyl acrylate, 2-(dimethylamino)ethyl methacrylate, 3-(dimethylamino)propyl methacrylamide, 3-(dimethylamino)propyl acrylamide, lysine, 3-methacrylamidopropyl-trimethyl-ammonium, 3-acrylamidopropyl-trimethyl-ammonium, diallyldimethylammonium, 2-(acryloyloxy)-N,N,N-trimethylethanaminium, methacryloyloxyethyl trimethylammonium, N,N-dimethylaminoethyl acrylate benzyl, N,N-dimethylaminoethyl methacrylate benzyl, and combinations thereof.

[0065] It is understood that 3-methacrylamidopropyl-trimethyl-ammonium, 3-acrylamidopropyl-trimethyl-ammonium, diallyldimethylammonium, 2-(acryloyloxy)-N,N,N-trimethylethanaminium, methacryloyloxyethyltrimethylammonium, N,N-dimethylaminoethyl acrylate benzyl, and N,N-dimethylaminoethyl methacrylate benzyl are typically provided with a counterion, such as a carboxylate or halide anion. For example, diallyldimethylammonium is typically provided as diallyldimethylammonium chloride (DADMAC). The disclosed embodiments are not limited with respect to the use of any particular counterion, unless the counterion is explicitly stated.

[0066] In certain embodiments, the non-polymeric compound preferably comprises lysine, methacryloyloxyethyltrimethylammonium, 2-(dimethylamino)ethyl methacrylate, diallyldimethylammonium, and mixtures thereof. In one embodiment disclosed below, the polishing composition advantageously comprises diallyldimethylammonium, and most preferably comprises DADMAC.

[0067] In use, the polishing composition may include substantially any suitable amount of the non-polymeric cationic compound (e.g., depending on the particular compound and other components used and the amounts of these components in the composition). In certain embodiments, the amount of the non-polymeric cationic compound may be from about 1 ppm to about 1000 ppm by weight (e.g., from about 2 ppm to about 500 ppm by weight, from about 5 ppm to about 200 ppm by weight, or from about 10 ppm to about 100 ppm by weight) at the point of use.

[0068] The polishing composition may further comprise a polishing rate control agent. The polishing rate control agent may be a polishing rate enhancer (e.g., enhance the polishing rate on an oxide pattern) or a polishing rate inhibitor (e.g., inhibit the polishing rate on a trench oxide). The polishing rate enhancer may comprise, for example, a carboxylic acid compound that activates the abrasive particles or the substrate. Suitable rate enhancers include, for example, picolinic acid, nicotinic acid, quinaldic acid, iso-nicotinic acid, acetic acid, and 4-hydroxybenzoic acid. As mentioned above, picolinic acid can function as a rate enhancer or inhibitor depending on the concentration, and may be advantageous in certain embodiments (e.g., as disclosed in the examples below).

[0069] The polishing composition may include substantially any suitable amount of the rate control agent. In one embodiment, the polishing composition includes from about 10 ppm (0.001 percent by weight) to about 1 percent by weight (e.g., from about 50 ppm to about 0.5 percent by weight, from about 100 ppm to about 0.25 percent by weight, or from about 200 ppm to about 1000 ppm by weight) of the rate control agent at the point of use.

[0070] The polishing composition may further include a removal rate inhibitor (e.g., a silicon nitride inhibitor), such as an unsaturated carboxylic acid, such as an unsaturated monoacid. Suitable unsaturated monoacids may include, for example, acrylic acid, 2-butenoic acid (crotonic acid), 2-pentenoic acid, trans-2-hexenoic acid, trans-3-hexenoic acid, 2-hexynoic acid, 2,4-hexadienoic acid, potassium sorbate, trans-2-methyl-2-butenoic acid, 3,3-dimethylacrylic acid, and combinations thereof, including stereoisomers thereof. In one embodiment disclosed below, the removal rate inhibitor is crotonic acid.

[0071] In use, the polishing composition may contain substantially any suitable amount of removal rate inhibitor (e.g., depending on the particular compounds and other components used and the amounts of these components in the composition). In certain embodiments, the amount of removal rate inhibitor may be about 10 ppm by weight to about 1 ppm by weight (10,000 ppm by weight) (e.g., about 20 ppm by weight to about 5,000 ppm by weight, about 50 ppm by weight to about 2,000 ppm by weight, or about 100 ppm by weight to about 1,000 ppm by weight) at the point of use.

[0072] The polishing composition may further comprise one or both of a pH adjuster and / or a pH buffer. The pH adjuster may be substantially any defined pH adjuster, such as an alkylamine, an alcoholamine, a quaternary amine hydroxide, ammonia, or a combination thereof. In certain embodiments, a suitable pH adjuster may comprise triethanolamine (TEA), tetramethylammonium hydroxide (TMAH or TMA-OH), or tetraethylammonium hydroxide (TEAH or TEA-OH). In one advantageous embodiment, the pH adjuster is triethanolamine. The polishing composition may comprise a sufficient concentration of a pH adjuster to achieve and / or maintain the pH of the polishing composition within the above pH range. In one embodiment, the polishing composition comprises about 100 ppm to about 1 weight percent of a pH adjuster (e.g., triethanolamine) at the point of use.

[0073] The polishing composition may include substantially any suitable buffering agent, such as phosphates, sulfates, acetates, malonates, oxalates, borates, ammonium salts, azoles, and the like. In certain advantageous embodiments, the pH buffering agent may include benzotriazole or bistrismethane. The polishing composition may include a pH buffering agent at a concentration sufficient to provide a desired buffering capacity at a pH within the above pH range. In certain embodiments, the polishing composition includes about 100 ppm to about 1 weight percent of a pH adjuster (e.g., triethanolamine) at the point of use.

[0074] The polishing composition may further include other optional additives, such as additives including secondary polishing rate accelerators or inhibitors, dispersants, conditioners, scale inhibitors, chelating agents, stabilizers, and biocides. Such additives are purely optional. The disclosed embodiments are not so limited and do not require the use of any one or more of such additives.

[0075] The polishing composition may further include a biocide. The biocide may include substantially any suitable biocide, such as an isothiazolinone biocide, such as methylisothiazolinone or benzisothiazolone. The amount of the biocide in the polishing composition is typically about 1 ppm to about 100 ppm by weight, such as about 5 ppm to about 75 ppm by weight, at the point of use.

[0076] The polishing composition can be prepared using any suitable technique. Many of these techniques are known to those skilled in the art. The polishing composition can be prepared in a batch or continuous process. Broadly speaking, the polishing composition can be prepared by combining its components in any order. As used herein, "component" includes individual ingredients (e.g., abrasive grains, autostopper, cationic polymer, and optional additives). For example, the autostopper and cationic polymer can be added to an aqueous carrier (e.g., water) at a desired concentration. The pH can then be adjusted (as desired) and the cubic ceria abrasive can be added at a desired concentration to form the polishing composition. The polishing composition can be prepared before use, in which case one or more components are added to the polishing composition immediately before use (e.g., within about 1 minute before use, or within about 1 hour before use, or about 1 day or about 7 days before use). The polishing composition can also be prepared by mixing the components at the substrate surface during the polishing operation (e.g., on a polishing pad).

[0077] In certain embodiments, the polishing composition can be provided as a "two-pack" system. For example, a first pack can include the cubic ceria abrasive, the rate control additive, and other optional ingredients, and a second pack can include the auto-stopper, the cationic polymer, and other optional ingredients. The first and second packs can be shipped separately and combined on the polishing pad prior to polishing (within an hour or day of polishing) or during the CMP operation.

[0078] The polishing composition of the present invention may be provided as a concentrate. The concentrate is intended to be diluted with an appropriate amount of water before use. In such an embodiment, the polishing composition concentrate can include cubic ceria abrasive particles and other components described above in such an amount that, when the concentrate is diluted with an appropriate amount of water, each component of the polishing composition is present in the polishing composition in an amount within the appropriate range described above for each component. For example, the cubic ceria abrasive particles, the auto-stopping agent, the cationic polymer, and other optional additives can each be present in the polishing composition in an amount that is about 3 times (e.g., about 4 times, about 5 times, about 6 times, about 7 times, about 8 times, about 10 times, about 15 times, about 20 times, or about 25 times) the point-of-use concentration described above for each component, so that when the concentrate is diluted with an equal volume of water (e.g., 2 equal volumes of water, 3 equal volumes of water, 4 equal volumes of water, 5 equal volumes of water, 6 equal volumes of water, 7 equal volumes of water, 9 equal volumes of water, 14 equal volumes of water, 19 equal volumes of water, or 24 equal volumes of water), each component will be present in the polishing composition in an amount within the range described above for each component.

[0079] In embodiments in which the polishing composition is provided as a two-pack system, one or both of the packs are provided as concentrates and require dilution before mixing with the other pack. For example, in one embodiment, the first pack is provided as a concentrate, such that the concentrate contains cubic ceria abrasive particles at a concentration about three times (e.g., about 5 times, about 8 times, about 10 times, about 15 times, or about 20 times) higher than the point-of-use concentrations described above. The concentrated first pack can be mixed with a suitable amount of water before combining with the second pack. Similarly, the second pack is provided as a concentrate, such that the concentrate contains autoclaving agent and cationic polymer concentrations about three times (e.g., about 5 times, about 8 times, about 10 times, about 15 times, or about 20 times) higher than the point-of-use concentrations described above. In such embodiments, the concentrated second pack can be mixed with a suitable amount of water before combining with the first pack. In certain embodiments, both the first pack and the second pack can be diluted with water before combining. The disclosed embodiments are not limited in this respect.

[0080] The polishing method of the present invention is particularly suitable for use with a chemical mechanical polishing (CMP) apparatus, for example, including a platen and a pad fixed to the platen. As known to those skilled in the art, when a substrate is contacted with the polishing pad and the polishing composition of the present invention, the substrate is polished, and then at least a portion of the substrate is ground by moving the polishing pad and the substrate relative to each other. The method of the present invention includes providing the composition of the present invention described above, contacting a substrate (e.g., a wafer) with the polishing composition of the present invention, moving the polishing composition relative to the substrate, and grinding the substrate, thereby removing a portion of the silicon oxide material from the substrate, thereby polishing the substrate.

[0081] The substrate generally includes a patterned dielectric layer, many of which are well known. The patterned dielectric layer includes various forms of silicon oxide and silicon oxide-based dielectric materials. For example, the dielectric materials including silicon oxide and silicon oxide-based dielectric layers include, consist of, or consist essentially of tetraethoxysilane (TEOS), high density plasma (HDP) oxide, phosphosilicate glass (PSG), borophosphosilicate glass (BPSG), high aspect ratio process (HARP) oxide, spin-on dielectric (SOD) oxide, chemical vapor deposition (CVD) oxide, plasma-assisted tetraethyl orthosilicate (PETEOS), thermal oxide, or undoped silicate glass.

[0082] The method of the present invention desirably planarizes the patterned dielectric material, for example, through reducing the initial step height between the raised regions (having an initial height) and the trench (having an initial trench thickness). To effectively and efficiently accomplish this planarization, the method of the present invention desirably has a high removal rate of the raised regions (of the active pattern dielectric material) and a significantly lower removal rate of the trench dielectric material. Most preferably, the method of the present invention also exhibits self-stopping behavior.

[0083] During the method of the present invention, dielectric material is removed from the raised regions (and less of it may be removed from the trenches). Planarization reduces the height of the raised regions so that they are essentially the same "level" as the trench height. Thus, for example, the step height can be reduced to less than 1,000 angstroms (Å), e.g., less than 800 Å, less than 500 Å, less than 300 Å, less than 250 Å. The surface is considered to be effectively planarized when the reduced (by polishing) step height (i.e., the "residual" step height) reaches less than about 1,000 Å.

[0084] Depending on the substrate being polished, the initial step height may be at least 1,000 Å, such as at least 2,000 Å, or at least 5,000 Å, and may be significantly greater, such as at least 10,000 Å, at least 20,000 Å, at least 30,000 Å, at least 40,000 Å, as measured before the start of the CMP process step.

[0085] During a CMP operation, the removal rate of the patterned dielectric material is referred to by those skilled in the art as the "pattern removal rate" or "active removal rate." The active removal rate achieved using the methods and polishing compositions described herein may be any suitable rate and will depend in large part on the selected polishing tool parameters and the dimensions (e.g., pitch and width) of the patterned dielectric material for any given process and substrate. In certain advantageous embodiments, the active removal rate is greater than about 4,000 Å / min (e.g., greater than about 5,000 Å / min, greater than about 6,000 Å / min, greater than about 10,000 Å / min).

[0086] The CMP operation of the present invention also desirably reduces trench loss. For example, methods of the present invention can provide trench loss of less than about 2,000 Å (e.g., less than about 1,500 Å, less than about 1,000 Å, less than about 500 Å, or less than about 250 Å).

[0087] Lower trench loss can be efficiently reflected in improved planarization. Planarization efficiency as used herein means step height reduction divided by trench loss. The planarization efficiency provided by the method of the present invention may be at least 4, preferably 5 or more than 10 (or more than 20, or more than 50).

[0088] The method of the present invention can also exhibit self-stopping behavior. By self-stopping, it is meant that the removal rate of the blanket-derived material is significantly lower than the removal rate of the pattern dielectric material. Self-stopping behavior is considered to occur when the removal rate of the blanket-derived material is less than about 1,000 Å / min. The method of the present invention can thus exhibit a blanket dielectric material removal rate of less than 1,000 Å / min (e.g., less than about 500 Å / min).

[0089] In another measurement, the auto-stop behavior can be measured by calculating the ratio of the active removal rate of the pattern dielectric material to the magnetic rate of the blanket dielectric material. A high ratio indicates good auto-stop behavior. The method of the present invention can thus produce a ratio of greater than about 5 (e.g., greater than about 10, greater than about 20, or greater than about 50).

[0090] Of course, the disclosure includes numerous embodiments, including but not limited to the following embodiments.

[0091] In a first embodiment, the chemical-mechanical polishing composition includes a liquid carrier, cubic abrasive particles dispersed in the liquid carrier, an autoclaving agent, and a cationic polymer.

[0092] A second embodiment may include the first embodiment, wherein the cubic ceria abrasive particles include a mixture of cerium oxide and lanthanum oxide.

[0093] A third embodiment may include any one of the first to second embodiments, wherein the cubic ceria abrasive particles have a molar ratio of lanthanum to lanthanum and cerium of about 1 to about 15 percent.

[0094] A fourth embodiment may include any one of the first to third embodiments, wherein the cubic ceria abrasive particles have a BET surface area of ​​about 3 m 2 / g ~ approx. 14m 2 / g.

[0095] A fifth embodiment may include any one of the first to fourth embodiments, wherein the cubic ceria abrasive particles have an average particle size of about 50 to about 500 nm.

[0096] A sixth embodiment may include any one of the first through fifth embodiments, including about 0.01 weight percent to about 1 weight percent cubic ceria abrasive particles.

[0097] A seventh embodiment may include any one of the first to sixth embodiments, wherein the auto-stopper is a ligand bonded to the cubic ceria abrasive particles.

[0098] An eighth embodiment may include any one of the first through seventh embodiments, wherein the auto-stopper has the formula QB, where Q is a substituted or unsubstituted hydrophobic group or a sterically hindering group, and B is a linking group attached to the cubic ceria abrasive particle. In such embodiments, the auto-stopper may include kojic acid, maltol, ethyl maltol, propyl maltol, hydroxamic acid, benzhydroxamic acid, salicylhydroxamic acid, benzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, caffeic acid, sorbic acid, potassium sorbate, and combinations thereof.

[0099] A ninth embodiment may include any one of the first to eighth embodiments, wherein the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof.

[0100] A tenth embodiment may include any one of the first to ninth embodiments, wherein the cationic polymer is selected from the group consisting of poly(vinylimidazolium), poly(vinylimidazole), methacryloyloxyethyltrimethylammonium, poly(diallyldimethylammonium), polyquaternium-2, polyquaternium-11, polyquaternium-16, polyquaternium-46, polyquaternium-44, polylysine, and combinations thereof.

[0101] An eleventh embodiment may include any one of the first to tenth embodiments, wherein the cationic polymer is poly(vinylimidazolium), poly(vinylimidazole), methacryloyloxyethyltrimethylammonium, polylysine, or a combination thereof.

[0102] A twelfth embodiment may include any one of the first to eleventh embodiments, wherein (i) the cubic ceria abrasive particles have a use point concentration of about 0.01 weight percent to about 1 weight percent, (ii) the autoclaving agent has a use point concentration of about 200 ppm to about 5000 ppm by weight, and (iii) the cationic polymer has a use point concentration of about 5 ppm to about 500 ppm by weight.

[0103] A thirteenth embodiment may include any one of the first to twelfth embodiments, further including a carboxylic acid rate enhancer.

[0104] A fourteenth embodiment may include any one of the first to thirteenth embodiments, wherein the carboxylic acid rate enhancer is picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof.

[0105] A fifteenth embodiment may include any one of the first through fourteenth embodiments, further including an unsaturated carboxylic monoacid rate inhibitor selected from the group consisting of acrylic acid, crotonic acid, 2-pentenoic acid, trans-2-hexenoic acid, trans-3-hexenoic acid, 2-hexynoic acid, 2,4-hexadienoic acid, potassium sorbate, trans-2-methyl-2-butenoic acid, 3,3-dimethylacrylic acid, and combinations thereof.

[0106] A sixteenth embodiment may include any one of the first to seventeenth embodiments, wherein the unsaturated carboxylic monoacid rate inhibitor is crotonic acid.

[0107] A seventeenth embodiment may include any one of the first through sixteenth embodiments and includes a non-polymeric cationic compound selected from the group consisting of 2-(dimethylamino)ethyl acrylate, 2-(dimethylamino)ethyl methacrylate, 3-(dimethylamino)propyl methacrylamide, 3-(dimethylamino)propyl acrylamide, lysine, 3-methacrylamidopropyl-trimethyl-ammonium, 3-acrylamidopropyl-trimethyl-ammonium, diallyldimethylammonium, 2-(acryloyloxy)-N,N,N-trimethylethanaminium, methacryloyloxyethyl trimethylammonium, N,N-dimethylaminoethyl acrylate benzyl, N,N-dimethylaminoethyl methacrylate benzyl, and combinations thereof.

[0108] An eighteenth embodiment can include any one of the first to seventeenth embodiments, wherein the non-polymeric cationic compound includes diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

[0109] A nineteenth embodiment may include any one of the first to eighteenth embodiments, wherein the cationic polymer includes polylysine and the non-polymeric compound includes diallyldimethylammonium.

[0110] A twentieth embodiment may include any one of the first to nineteenth embodiments, further including a pH adjuster comprising an alkylamine, an alcoholamine, a quaternary amine hydroxide, ammonia, or a combination thereof. The pH adjuster may include, for example, triethanolamine.

[0111] The twenty-first embodiment may include any one of the first to twentieth embodiments, and further includes benzotriazole or bistrismethane.

[0112] A twenty-second embodiment may include any one of the first to twenty-first embodiments, wherein the pH is about 5 to about 10.

[0113] A twenty-third embodiment may include any one of the first to twenty-second embodiments, wherein (i) the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof, (ii) the cationic polymer is poly(vinylimidazolium), poly(methacryloyloxyethyltrimethylammonium), polylysine, poly(diallyldimethylammonium), or a combination thereof, and (iii) the composition further comprises picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof.

[0114] A twenty-fourth embodiment may include the twenty-third embodiment, further including triethanolamine and benzotriazole.

[0115] A twenty-fifth embodiment may include any one of the twenty-third or twenty-fourth embodiments, wherein the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof, and the pH is about 7 to about 9 at the point of use.

[0116] A twenty-sixth embodiment may include any one of the twenty-third to twenty-fifth embodiments, including at least 250 ppm by weight of the point-of-use autoclaving agent and 50 ppm by weight of the point-of-use cationic polymer.

[0117] A twenty-seventh embodiment may include the twenty-third embodiment, wherein the autostop agent is kojic acid, potassium sorbate, or a combination thereof, and the pH is from about 5 to about 6.5 at the point of use.

[0118] A twenty-eighth embodiment may include any one of the first to twenty-second embodiments, wherein (i) the autoterminating agent is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof, and (ii) the cationic polymer is ε-poly-L-lysine, poly(vinylimidazolium), or a combination thereof.

[0119] The twenty-ninth embodiment may include the twenty-eighth embodiment, further including crotonic acid.

[0120] A thirtieth embodiment may include any one of the twenty-eight or twenty-ninth embodiments, further including a non-polymeric cationic compound selected from the group consisting of diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

[0121] A thirty-first embodiment may include the thirtieth embodiment and includes at least 250 ppm by weight of the autostop agent, at least 20 ppm by weight of the cationic polymer, and at least 20 ppm by weight of the non-polymeric cationic compound.

[0122] A thirty-second embodiment includes a method for chemical-mechanical polishing a substrate comprising a silicon oxide dielectric material, the method including (a) providing a polishing composition comprising any one of the first through thirty-first embodiments, (b) contacting the substrate with the provided polishing composition, (c) moving the polishing composition relative to the substrate, and (d) ablating the substrate to remove a portion of the silicon oxide dielectric material from the substrate, thereby polishing the substrate.

[0123] A thirty-third embodiment may include the thirty-second embodiment, further comprising: active removal of the silicon oxide dielectric material in patterned areas of the substrate versus trench loss removal of the silicon oxide dielectric material. Ratio of However, in (d), it is more than about 5.

[0124] A thirty-fourth embodiment may include any one of the thirty-second to thirty-third embodiments, wherein the auto-stop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof, the cationic polymer is poly(vinylimidazolium), poly(methacryloyloxyethyltrimethylammonium), polylysine, poly(diallyldimethylammonium), or a combination thereof, and the polishing composition further comprises picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof.

[0125] A thirty-fifth embodiment may include any one of the thirty-second to thirty-third embodiments, wherein the auto-stopper is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof, and the cationic polymer is ε-poly-L-lysine, poly(vinylimidazolium), or a combination thereof.

[0126] A thirty-sixth embodiment may include the thirty-second, thirty-third, or thirty-fourth embodiment, and further includes a non-polymeric cationic compound selected from the group consisting of diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

[0127] A thirty-seventh embodiment may include the thirty-fifth or thirty-sixth embodiment, further comprising: active removal of the silicon oxide dielectric material in patterned areas of the substrate versus trench loss removal of the silicon oxide dielectric material. Ratio of However, in (d), it is more than about 50.

[0128] A thirty-eighth embodiment can include any one of the thirty-second through thirty-seventh embodiments, wherein preparing the polishing composition includes (i) providing a polishing concentrate, and (ii) diluting the polishing concentrate with at least one part water to one part polishing concentrate to obtain the polishing composition.

[0129] A 39th embodiment can include any one of the 32nd to 37th embodiments, and preparing the polishing composition includes (i) preparing a first pack and a second pack, the first pack containing cubic ceria abrasive particles and the second pack containing an autoclaving agent and a cationic polymer, and (ii) combining the first pack and the second pack to obtain the polishing composition.

[0130] A fortieth embodiment can include the thirty-ninth embodiment, wherein at least one of the first pack and the second pack is diluted with water prior to combining in (ii). EXAMPLES

[0131] The following examples further illustrate the invention, but should not be construed as limiting its scope in any way. Various substrates were polished using an Applied Materials Mirra® polishing tool (available from Applied Materials, Inc.). Blanket wafers were polished for 60 seconds on the Mirra® with a platen speed of 100 rpm, a head speed of 85 rpm, a downforce of 3 psi, and a slurry flow rate of 150 ml / min. Patterned wafers were polished for 80 seconds under the same conditions. Wafers were polished on a NexPlanar® E6088 pad (available from Cabot Microelectronics Corporatio) with in-situ conditioning using a Saesol DS8051 conditioner with 6 pounds downforce.

[0132] Blanket tetraethyl orthosilicate (TEOS), blanket SiN, and patterned TEOS were polished in the following examples. Blanket TEOS wafers were obtained from WRS Materials and contained a 20 kÅ TEOS layer. Blanket SiN wafers were obtained from Advantec and contained a 5 kÅ PE SiN layer. Patterned TEOS wafers were 10 kÅ TEOS patterned wafers from Silyb and STI1.

[0133] Example 1 A raw cerium oxide dispersion was prepared as follows: A cerium nitrate solution was prepared by combining 13.1 kg of 3M cerium(III) nitrate solution, 0.3 kg of 3M lanthanum nitrate solution, 2.0 kg of 68% nitric acid (HNO3) solution, 0.5 kg of deionized water, and cerium(IV) nitrate at a molar ratio of cerium(IV) to cerium (total) of 0.000055. The cerium nitrate solution was then degassed in a 20 L vessel by stirring and bubbling with nitrogen.

[0134] An aqueous ammonia solution was prepared by combining 75 kg of deionized water with 13.1 kg of a 25% aqueous ammonia solution (which resulted in a molar ratio of NH4OH in the aqueous ammonia solution to the total amount of cerium and lanthanum in the cerium nitrate solution of 9.0). The aqueous ammonia solution was then degassed in a 100 L jacketed reactor by stirring and bubbling with nitrogen.

[0135] The cerium nitrate solution was then added to the aqueous ammonia solution at ambient temperature with the same stirring under a nitrogen purge. The temperature of the reaction mixture was then increased to 80° C. and held at that temperature for 18 hours. The reaction mixture was then allowed to cool and, once cooled, was acidified to pH 2 by the addition of 68% nitric acid.

[0136] The reaction mixture was then filtered and washed with deionized water. The washing was repeated when the conductivity of the washing solution was less than 0.04 mS / cm. The final cerium oxide concentration was adjusted to 10 weight percent by adding deionized water. The cubic ceria abrasive particles contained 2.5 mole percent lanthanum oxide and 97.5 mole percent cerium oxide.

[0137] Nitrogen adsorption increases the BET specific surface area to 11.8 m 2 The average particle size was determined to be 102 nm as measured by a Horiba 960 and 140 nm as measured by a Malvern Zetasizer.

[0138] Example 2 Two polishing compositions were tested to evaluate the TEOS removal rate and auto-stop behavior on blanket and patterned wafers. Each composition was prepared by combining a first pack (A pack) with deionized water and a corresponding second pack (B pack). The A pack contained 3500 ppm by weight of picolinic acid, 75 ppm by weight of Kordex MLX, and 2 percent by weight of ceria abrasive at pH 4.0. For composition 2A, the ceria abrasive contained 2 percent by weight of control ceria (sintered ceria abrasive used in polishing composition 1C of commonly assigned U.S. Pat. No. 9,505,952). For composition 2B, the ceria abrasive contained 1 part by weight of the raw ceria dispersion described above in Example 1 and 4 parts by weight of deionized water to obtain 2% by weight of cubic ceria. The B pack was identical and contained 4000 ppm by weight triethanolamine, 1600 ppm by weight benzotriazole, 250 ppm by weight polyMADQUAT, 1670 ppm by weight benzhydroxamic acid, and 113 ppm by weight Kordex MLX at a pH of 8.2.

[0139] One part of the A pack was first combined with 6 parts of deionized water and then further combined with 3 parts of the B pack to obtain a point-of-use composition containing 0.2 weight percent ceria abrasive, 350 ppm picolinic acid, 1200 ppm triethanolamine, 480 ppm benzotriazole, and 75 ppm polyMADQUAT by weight. The pH of the combined A and B packs was about 7.8.

[0140] Blanket TEOS wafers were polished on the Mirra® tool for 60 seconds under the above conditions. The blanket TEOS removal rates are shown in Table 1 in angstroms per minute (Å / min). Patterned wafers were polished on the Mirra® tool for 80 seconds under the same conditions. The results for the patterned wafers (trench loss, active removal, and step height) are also shown in Table 1. Step heights are listed in angstroms (Å) for two pattern features (the first number refers to the line width in microns and the second number refers to the pattern density). [Table 1]

[0141] As is readily apparent from the results shown in Table 1, the composition containing cubic ceria abrasive particles (2B) achieved a 65% improvement in active removal and improved step height (specifically in dense features). However, these improvements were offset by a nearly 10-fold increase in trench loss. Due to the high blanket removal rate and high trench loss, composition 2B (containing cubic ceria abrasive particles) is not a self-stopping composition. Based on this example, it is readily apparent to one skilled in the art that conventional wetted ceria abrasive particles (as in 2A) cannot be substituted for cubic ceria abrasive particles (as in 2B) in a self-stopping CMP composition due to the complex interactions between the ceria abrasive and the composition chemistry.

[0142] Example 3 Ten polishing compositions were tested to evaluate the TEOS polishing rate and auto-stop behavior on patterned wafers. Ten polishing compositions (3A-3J) were selected to vary the cationic polymer level and compared with the control composition 1A. Each composition was prepared by combining the A pack with deionized water and the corresponding B pack. Each A pack contained 3500 ppm by weight picolinic acid, 75 ppm by weight Kordex MLX, and 20 percent by weight of the ceria dispersion described above in Example 1 (for a total ceria concentration of 2 percent by weight in the A pack).

[0143] The B pack contained 4000 ppm by weight triethanolamine, 1600 ppm by weight benzotriazole, cationic polymer, 1670 ppm by weight benzhydroxamic acid, and 113 ppm by weight Kordex MLX at a pH of 8.2. The type and amount of cationic polymer are listed in Table 2A below. [Table 2A]

[0144] One part of the A pack was first combined with 6 parts of deionized water, and then further combined with 3 parts of the B pack to obtain a point-of-use composition containing 0.2 weight percent ceria abrasive, 350 ppm picolinic acid, 1200 ppm triethanolamine, 500 ppm benzhydroxamic acid, and 480 ppm benzotriazole. The point-of-use amount of cationic polymer was 30 percent of the amount listed in Table 2A. The pH of the combined A and B packs was about 7.8.

[0145] A blanket TEOS wafer was polished on the Mirra® tool for 60 seconds under the above conditions. The blanket TEOS removal rate is shown in Table 2B in angstroms per minute (Å / min). A patterned wafer was polished on the Mirra® tool for 80 seconds under the same conditions. The results (trench loss, active removal, and step height) for the patterned wafer are also shown in Table 2B. The step height is listed in angstroms (Å) for the two patterns (the first number refers to the line width in microns, and the second number refers to the pattern density). [Table 2B]

[0146] As is readily apparent from the results shown in Table 2B, compositions 3B and 3E, which include polyMADQUAT and polyquaternium-44 cationic polymers, provide excellent auto-stop performance. Additionally, compositions 3C, 3F, and 3J provide excellent ratios of active removal rate to both blanket removal rate and trench loss. With minor modifications, these compositions provide similarly excellent auto-stop performance.

[0147] Example 4 Eight polishing compositions were tested to evaluate the TEOS removal rate and autostop behavior on patterned wafers. Eight polishing compositions (3A-3J) were selected to vary the autostop level and were compared with the control composition 2A. Each composition was prepared by combining the A pack with deionized water and the corresponding B pack. Each A pack contained 3500 ppm by weight picolinic acid, 75 ppm by weight Kordex MLX, and 20 percent by weight of the ceria dispersion described above in Example 1 (for a total ceria concentration of 2 percent by weight in the A pack).

[0148] The B pack contained 4000 ppm by weight triethanolamine, 1600 ppm by weight benzotriazole, 250 ppm by weight PolyMADQUAT, an autostopper, and 113 ppm by weight Kordex MLX. The types and amounts of the autostopper are listed in Table 3A below. [Table 3A]

[0149] One part of the A pack was first combined with 6 parts of deionized water and then further combined with 3 parts of the B pack to obtain a point-of-use composition containing 0.2 weight percent ceria abrasive, 350 ppm picolinic acid, 1200 ppm triethanolamine, 75 ppm polyMADQUAT, and 480 ppm benzotriazole. The point-of-use amount of autostop was 30 percent of the amount listed in Table 3A. The pH of the combined A and B packs was about 7.8 for compositions 4A-4D and about 5.5 for compositions 4E-4H.

[0150] Blanket TEOS wafers were polished on the Mirra® tool for 60 seconds under the above conditions. The blanket TEOS removal rates are shown in Table 3B in angstroms per minute (Å / min). Patterned wafers were polished on the Mirra® tool for 80 seconds under the same conditions. The results for the patterned wafers (trench loss, active removal, and step height) are also shown in Table 3B. Step heights are listed in angstroms (Å) for two pattern features (the first number refers to the line width in microns, and the second number refers to the pattern density). [Table 3B]

[0151] As is readily apparent from the results shown in Table 3B, compositions 4B, 4D and 4H, which include benzhydroxamic acid, salicylhydroxamic acid and potassium sorbate autostop agents, provide excellent autostop performance. Additionally, composition 4F provides an excellent ratio of active removal rate to both blanket removal rate and trench loss. With minor modifications, this composition provides similarly excellent autostop performance.

[0152] Example 5 Two polishing compositions were tested to evaluate the TEOS polishing rate and auto-stop behavior on blanket and patterned wafers. Each composition was prepared by combining a first pack (A pack) with deionized water and a corresponding second pack (B pack). The A pack contained 3500 ppm by weight of picolinic acid, 75 ppm by weight of Kordex MLX, and 2 percent by weight of ceria abrasive at pH 4.0. For composition 5A, the ceria abrasive contained 2 percent by weight of control ceria (the sintered ceria abrasive used in polishing composition 1C of commonly assigned U.S. Pat. No. 9,505,952). For composition 5B, the ceria abrasive contained 1 part by weight of the raw ceria dispersion described above in Example 1 and 4 parts by weight of deionized water. The B pack was identical and contained 4000 ppm by weight triethanolamine, 1600 ppm by weight benzotriazole, 250 ppm by weight polyMADQUAT, 3340 ppm by weight potassium sorbate, and 113 ppm by weight Kordex MLX at a pH of 6.

[0153] One part of the A pack was first combined with 6 parts deionized water and then further combined with 3 parts of the B pack to obtain a point-of-use composition containing 0.2 weight percent ceria abrasive, 350 ppm picolinic acid, 1200 ppm triethanolamine, 480 ppm benzotriazole, 1000 ppm potassium sorbate, and 75 ppm polyMADQUAT. The pH of the combined A and B packs was about 5.5.

[0154] Blanket TEOS wafers were polished on the Mirra® tool for 60 seconds under the above conditions. The blanket TEOS removal rates are shown in Table 4 in angstroms per minute (Å / min). Patterned wafers were polished on the Mirra® tool for 80 seconds under the same conditions. The results for the patterned wafers (trench loss, active removal, and step height) are also shown in Table 4. [Table 4]

[0155] As is readily apparent from the results shown in Table 4, the composition containing the cubic ceria abrasive particles (2B) achieved excellent self-stop performance. The active to blanket removal ratio was greater than 12, and the step height was less than 400 Å on dense features. In contrast, the composition using the control ceria abrasive exhibited extremely low removal rates and did not result in planarization of the patterned wafer.

[0156] Example 6 Six polishing compositions were tested to evaluate the active loss on patterned wafers across a variety of patterns. As known to those skilled in the art, active loss is defined as the active thickness before polishing minus the active thickness after polishing. The polishing compositions were identical to compositions 2A, 3B, 3E, 4B, 4D, and 4H. As noted above, composition 2B contained a control ceria abrasive, while compositions 3B, 3E, 4B, 4D, and 4H contained cubic ceria abrasive particles. The active loss was plotted in Å against the type of pattern in FIG. 4.

[0157] As is readily apparent from the results shown in Figure 4, the compositions containing cubic ceria abrasive particles achieve superior planarization as defined by greater active loss across a variety of pattern densities. Additionally, the compositions containing cubic ceria abrasive particles also achieve superior planarization as defined by the difference between the maximum and minimum plot active losses across a variety of pattern densities. Without wishing to be bound by theory, it is believed that the cubic ceria abrasive particles perform better with higher concentrations of auto-stopper and / or cationic polymer, thus achieving superior planarization.

[0158] Example 7 Two polishing compositions were tested to evaluate the TEOS and SiN polishing rate and auto-stop behavior on blanket and patterned wafers. Each of compositions 7A, 7B, and 7C was prepared by combining the polishing formulation (A pack) with the corresponding additive formulation (B pack) in a 7:3 volume ratio. The use point pH of each composition was 6.2. The composition of the polishing formulation (A pack) is shown in Table 5A, while the composition of the additive formulation (B pack) is shown in Table 5B. All compositions are based on weight (e.g., weight percent or weight ppm). [Table 5A] [Table 5B]

[0159] Blanket TEOS and SiN wafers were polished on an Applied Materials Reflexion tool for 60 seconds using a DuPont IC1010 pad with a platen speed of 73 rpm, a head speed of 67 rpm, a down force of 3.5 psi, and a slurry flow rate of 250 ml / min. The removal rates of blanket TEOS and SiN are shown in Table 5C in angstroms per minute (Å / min). Patterned wafers were polished on the Reflexion tool under the same conditions for 20 seconds. The results for the patterned wafers (trench loss, and active removal) are also shown in Table 5C. [Table 5C]

[0160] As is readily apparent from the results shown in Table 5C, composition 7B exhibits excellent auto-stop performance, with a high amount of active removal (near 4000 Å) and a very low blanket removal rate, resulting in an active removal ratio to blanket of nearly 100 and an active removal ratio to trench loss of 14. Composition 7C also exhibits excellent auto-stop performance, despite a low amount of active removal. The ratios of active removal to blanket and active removal to trench loss achieved by composition 7C were greater than 100.

[0161] Example 8 Three compositions were tested to evaluate the effect of the level of lanthanum doping in the cubic ceria abrasive particles on the TEOS removal rate. Composition 8A contained 0.28 weight percent of control ceria (wet process ceria HC60® commercially available from Rhodia). Composition 8B contained 0.28 weight percent of cubic ceria abrasive particles containing 2.5 mole percent lanthanum oxide and was prepared by diluting the raw ceria dispersion described above in Example 1 with 34 parts water to 1 part raw ceria dispersion. Composition 8C contained 0.28 weight percent of cubic ceria abrasive particles containing 10 mole percent lanthanum oxide and was prepared by diluting the ceria dispersion described in the following paragraph with 34 parts water to 1 part ceria dispersion. The pH of each of compositions 8A-8C was 4.

[0162] A cerium oxide dispersion was prepared as follows: A cerium nitrate solution was prepared by combining 11.5 kg of 3M cerium(III) nitrate solution, 1.3 kg of 3M lanthanum nitrate solution, 1.86 kg of 68% nitric acid (HNO3) solution, 0.5 kg of deionized water, and cerium(IV) nitrate in a molar ratio of cerium(IV) to cerium (total) of 0.0000125 (1 / 80,235). The cerium nitrate solution was then degassed in a 20 L vessel by stirring and bubbling with nitrogen.

[0163] An aqueous ammonia solution was prepared by combining 70 kg of deionized water with 14 kg of a 25% aqueous ammonia solution (which resulted in a molar ratio of NH4OH in the aqueous ammonia solution to the total amount of cerium and lanthanum in the cerium nitrate solution of 10). The aqueous ammonia solution was then degassed in a 100 L jacketed reactor by stirring and bubbling with nitrogen.

[0164] The cerium nitrate solution was then added to the aqueous ammonia solution at ambient temperature with the same stirring under a nitrogen purge. The temperature of the reaction mixture was then increased to 88° C. and held at that temperature for 13.5 hours. The reaction mixture was then allowed to cool and, once cooled, was acidified to pH 2 by the addition of 68% nitric acid.

[0165] The reaction mixture was then filtered and washed with deionized water. The washing was repeated when the conductivity of the washing solution was less than 0.04 mS / cm. The final cerium oxide concentration was adjusted to 10 weight percent by adding deionized water. The cubic ceria abrasive particles contained 10 mole percent lanthanum oxide and 90 mole percent cerium oxide.

[0166] Nitrogen adsorption increases the BET specific surface area to 8.6 m 2 The average particle size was determined to be 142 nm as measured by a Malvern Zetasizer.

[0167] A blanket TEOS wafer was polished on a Mirra® tool for 60 seconds under the above conditions. The polishing results are shown in Table 6. All removal rates (RR) are listed in angstroms per minute (Å / min). [Table 6]

[0168] As is readily apparent from the data presented in Table 5, compositions 8B and 8C exhibited comparable TEOS removal rates that were more than 1.6 times the removal rate of composition 8A.

[0169] When "a" and "an" and "the" and similar referents are used in the context of describing the present invention, they should be construed to cover both the singular and the plural unless otherwise indicated or clearly contradicted by context. The terms "comprising", "having", "including" and "containing" should be construed as open-ended terms (i.e., "including, but not limited to") unless otherwise indicated. The recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated, and each separate value is incorporated herein as if it were individually set forth herein. All methods described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. Any and all examples or language denoting examples (e.g., "such as") provided herein are merely intended to better illustrate the invention. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the invention.

[0170] Preferred embodiments of the invention are described herein, including the best mode known to the inventors for carrying out the invention. Variations of these preferred embodiments may become apparent to those of ordinary skill in the art upon reading the foregoing description. The inventors contemplate that such variations may be adopted by those of ordinary skill in the art as necessary, and the inventors intend for the invention to be practiced otherwise than as specifically described herein. Accordingly, this invention includes all modifications and equivalents of the subject matter recited in the claims appended hereto as permitted by applicable law. Furthermore, any combination of the above-described elements in all possible variations thereof is encompassed by the invention unless otherwise indicated herein or otherwise clearly contradicted by context.

[0171] Of course, the disclosure includes numerous embodiments beyond those contained in the above examples, including, but not limited to, the aspects recited in the appended claims.

Claims

1. 1. A chemical mechanical polishing composition comprising: A liquid carrier; cubic ceria abrasive particles dispersed in the liquid carrier, the cubic ceria abrasive particles comprising a mixture of cerium oxide and lanthanum oxide. an auto-stop agent, said auto-stop agent being kojic acid, maltol, ethyl maltol, propyl maltol, hydroxamic acid, benzhydroxamic acid, salicylhydroxamic acid, benzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, caffeic acid, sorbic acid, potassium sorbate, and combinations thereof; Cationic polymer 1. A chemical mechanical polishing composition comprising:

2. 10. The composition of claim 1, wherein the cubic ceria abrasive particles have a molar ratio of lanthanum to lanthanum and cerium of about 1 to about 15 percent.

3. The cubic ceria abrasive particles are about 3 mm in size. 2 / g ~ approx. 14m 2 The composition of claim 1 having a BET surface area in the range of 1 / g.

4. 10. The composition of claim 1, wherein the cubic ceria abrasive particles have an average particle size ranging from about 50 to about 500 nm.

5. 10. The composition of claim 1 comprising from about 0.01 weight percent to about 1 weight percent of cubic ceria abrasive particles.

6. 10. The composition of claim 1, wherein the auto-stop agent is a ligand attached to the cubic ceria abrasive particles.

7. 2. The composition of claim 1, wherein the auto-stop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof.

8. 2. The composition of claim 1, wherein the cationic polymer is selected from the group consisting of poly(vinylimidazolium), poly(vinylimidazole), methacryloyloxyethyltrimethylammonium, poly(diallyldimethylammonium), polyquaternium-2, polyquaternium-11, polyquaternium-16, polyquaternium-46, polyquaternium-44, polylysine, and combinations thereof.

9. 9. The composition of claim 8, wherein the cationic polymer is poly(vinylimidazolium), poly(vinylimidazole), methacryloyloxyethyltrimethylammonium, polylysine, or a combination thereof.

10. the cubic ceria abrasive particles have a point-of-use concentration of about 0.01 weight percent to about 1 weight percent; the autostop agent has a point-of-use concentration of about 200 ppm to about 5000 ppm by weight; and The cationic polymer has a point-of-use concentration of about 5 ppm by mass to about 500 ppm by mass; The composition of claim 1.

11. The composition of claim 1 further comprising a carboxylic acid speed enhancer.

12. The composition of claim 11, wherein the carboxylic acid speed enhancer is picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof.

13. 10. The composition of claim 1, further comprising an unsaturated monocarboxylic acid rate inhibitor selected from the group consisting of acrylic acid, crotonic acid, 2-pentenoic acid, trans-2-hexenoic acid, trans-3-hexenoic acid, 2-hexynoic acid, 2,4-hexadienoic acid, potassium sorbate, trans-2-methyl-2-butenoic acid, 3,3-dimethylacrylic acid, and combinations thereof.

14. 14. The composition of claim 13, wherein the unsaturated monocarboxylic acid rate inhibitor is crotonic acid.

15. 10. The composition of claim 1, comprising a non-polymeric cationic compound selected from the group consisting of 2-(dimethylamino)ethyl acrylate, 2-(dimethylamino)ethyl methacrylate, 3-(dimethylamino)propyl methacrylamide, 3-(dimethylamino)propyl acrylamide, lysine, 3-methacrylamidopropyl-trimethyl-ammonium, 3-acrylamidopropyl-trimethyl-ammonium, diallyldimethylammonium, 2-(acryloyloxy)-N,N,N-trimethylethanaminium, methacryloyloxyethyltrimethylammonium, N,N-dimethylaminoethyl acrylate benzyl, N,N-dimethylaminoethyl methacrylate benzyl, and combinations thereof.

16. 16. The composition of claim 15, wherein the non-polymeric cationic compound comprises diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

17. 16. The composition of claim 15, wherein the cationic polymer comprises polylysine and the non-polymeric compound comprises diallyldimethylammonium.

18. The composition of claim 1 further comprising triethanolamine.

19. The composition of claim 1 further comprising a benzotriazole or a bistrismethane.

20. The composition of claim 1 , wherein the pH is in the range of about 5 to about 10.

21. the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof; the cationic polymer is poly(vinylimidazolium), poly(methacryloyloxyethyltrimethylammonium), polylysine, poly(diallyldimethylammonium), or a combination thereof; and The composition of claim 1 , wherein the composition further comprises picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof.

22. 22. The composition of claim 21 further comprising triethanolamine and benzotriazole.

23. 22. The composition of claim 21, wherein the auto-stop agent is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof, and the pH ranges from about 7 to about 9 at the point of use.

24. 24. The composition of claim 23 comprising at least 250 ppm by weight at point of use of the autostop agent and 50 ppm by weight at point of use of the cationic polymer.

25. 22. The composition of claim 21, wherein the auto-stopper is kojic acid, potassium sorbate, or a combination thereof, and has a pH ranging from about 5 to about 6.5 at the point of use.

26. the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof; and the cationic polymer is ε-poly-L-lysine, poly(vinylimidazolium), or a combination thereof; The composition of claim 1.

27. 27. The composition of claim 26, further comprising crotonic acid.

28. 27. The composition of claim 26, further comprising a non-polymeric cationic compound selected from the group consisting of diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

29. at least 250 ppm by weight of said autostop agent; at least 20 ppm by weight of said cationic polymer; at least 20 ppm by weight of said non-polymeric cationic compound; 30. The composition of claim 28 comprising:

30. 1. A method for chemical mechanical polishing a substrate comprising a silicon oxide dielectric material, the method comprising: (a) providing a polishing composition comprising a liquid carrier, cubic ceria abrasive particles dispersed in the liquid carrier, a self-stopping agent, and a cationic polymer, wherein the cubic ceria abrasive particles comprise a mixture of cerium oxide and lanthanum oxide, and the self-stopping agent is selected from the group consisting of kojic acid, maltol, ethyl maltol, propyl maltol, hydroxamic acid, benzhydroxamic acid, salicylhydroxamic acid, benzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, caffeic acid, sorbic acid, potassium sorbate, and combinations thereof; (b) contacting the substrate with the provided polishing composition; (c) moving the polishing composition relative to the substrate; and (d) grinding the substrate to remove a portion of the silicon oxide dielectric material from the substrate, thereby polishing the substrate.

16. A method for chemical mechanical polishing a substrate comprising a silicon oxide dielectric material, comprising:

31. 31. The method of claim 30, wherein a ratio of active removal of the silicon oxide dielectric material in patterned areas of the substrate to trench loss removal of the silicon oxide dielectric material is greater than about 5 in step (d).

32. the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, kojic acid, potassium sorbate, or a combination thereof; the cationic polymer is poly(vinylimidazolium), poly(methacryloyloxyethyltrimethylammonium), polylysine, poly(diallyldimethylammonium), or a combination thereof; and the polishing composition further comprises picolinic acid, acetic acid, 4-hydroxybenzoic acid, or a mixture thereof; 31. The method of claim 30.

33. the autostop agent is benzhydroxamic acid, salicylhydroxamic acid, or a combination thereof; the cationic polymer is ε-poly-L-lysine, poly(vinylimidazolium), or a combination thereof; 31. The method of claim 30.

34. 34. The method of claim 33, wherein the polishing composition further comprises a non-polymeric cationic compound selected from the group consisting of diallyldimethylammonium, methacryloyloxyethyltrimethylammonium, lysine, 2-(dimethylamino)ethyl methacrylate, or a mixture thereof.

Citation Information

Patent Citations

  • Rare earth element cerium composite oxide particle and manufacturing method therefor and polishing composition

    JP2017186196A

  • Cerium oxide abrasive grain

    JP2018109089A

  • Self-stopping polishing composition and method for bulk oxide planarization

    WO2018194792A1